Body mass index changes in relation to male reproductive hormones: longitudinal results from a community-based cohort study - Ye, Yun; Liang, Qun-Feng; Li, Jian-Hui; Zheng, Jun-Biao; Yu, Xiao-Hua; Zhang, Shu-Cheng; Zhou, Wei-Jin; Shi, Hui-Juan; Liang, Guo-Qing; Zhu, Qian-Xi (American journal of men's health, 2021)
The objective of the current study was to explore the relationship between longitudinal change in body mass index (BMI) and reproductive hormones in middle-aged and elderly Chinese men. A cohort study was conducted in a rural area of China. Local male residents aged 40-80 years were recruited at baseline in 2012 and were followed up in 2016. Information about weight, height, waist circumference, sex hormones, smoking status, and medical history were obtained. The change in BMI reported no significant relationship with the change in total testosterone (TT), calculated free testosterone (cFT), and bioavailable testosterone (BioT) in Pearson correlation analyses. When the change in BMI was divided into three groups—“great loss,” “normal fluctuation,” and “great gain”—TT, cFT and BioT had the highest increase (or the lowest decrease) in men with “normal fluctuation” in BMI compared with the other two groups. The advantage of maintaining a stable BMI was more evident for those who were overweight, non-smoking, and disease-free. There was a tendency of a continuous increase in cFT and BioT with BMI increase in smoking and diseased populations. Maintaining a stable BMI is associated with maintaining normal levels of reproductive hormones, especially in overweight, non-smoking, and healthy men aged over 40 years.